GE_GERICHTE P/19725/2022 vom 30. Juni 2025 - GE Cour de justice (2025)
BRIGANDAGE;CHANTAGE;CONTRAINTE(DROIT PÉNAL);MENACE(DROIT PÉNAL);VOIES DE FAIT;VOL(DROIT PÉNAL);INFRACTIONS CONTRE LE DOMAINE SECRET;UTILISATION FRAUDULEUSE D'UN ORDINATEUR;TORT MORAL;FIXATION DE LA PEINE | CP.181; CP.139.al1; CP.140; CP.156.ch1; CP.126.al1; CP.183.al1.ch1; CP.180.al1; CP.179quater.al1; CP.147.al1; CO.49